Robust controller design for turning operations based on measured frequency response functions. Issue 1 (July 2017) - Hajdu, David; Insperger, Tamas; Stepan, Gabor
Abstract: One of the most significant limitation of the productivity of machining operations is the regenerative machine tool vibration, also called machine tool chatter, which is a self-excited vibration between the tool and the workpiece induced by the chip formation mechanism. Extension of the chatter-free parameters is possible by active chatter control techniques. The design of the controller requires the identification of the dynamic properties of the system. Uncertainties in the system parameters may result in an inappropriate control performance. Robust control design is therefore a necessary step during the optimization of machining operations. In this paper, a fast and efficient method is presented to determine the region of control gains in the presence of uncertainties in the measured frequency response functions. The method is based on the concept of structured singular values.